Morbidity and mortality pattern of low birth weight babies - Basnet, S; Adhikari, RK; Shrestha, PS (Journal of Institute of Medicine Nepal, 2009)
Background: The Neonatal Unit, established in 1984 provides Level II care. The increase in preterm births from 25% to 42% with 21% of perinatal deaths related to immaturity and it's consequences at birth prompted this study on low birth weight babies. Methods: A retrospective study was done for all babies admitted from 2058 to 2061B.S. Results: Of 1 327 babies, 29% were LBW with 62% being preterm. Increasing trends in babies < 1500gms and < 28 weeks at birth was noted. 70% were discharged, 10% referred (61% for advanced respiratory support) and 20% died. Respiratory distress and presumed sepsis were the most common reasons for admission as well as for deaths in LBW. Conclusion: The existing Neonatal Unit facilities have become inadequate to deal with the increased number, morbidity and mortality pattern of inborn LBW babies. The unit needs to be upgraded to Level III with provision for mechanical ventilation, early use of nasal CPAP and institution of effective infection control measures to improve survival of this high risk group Key words: Low birth weight, Neonatal unit, facilities Journal of Institute of Medicine, August, 2008; 30:2 6-10 The full text of this paper is available from the Journal of Institute of Medicine website